2014
DOI: 10.1177/1040638714555898
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and genetic characterization of an Actinobacillus pleuropneumoniae serovar K12:O3 strain

Abstract: An atypical Actinobacillus pleuropneumoniae serovar 12 strain, termed QAS106, was isolated from a clinical case of porcine pleuropneumonia in Japan. An immunodiffusion (ID) test identified the strain as serovar 12. However, the ID test also demonstrated that strain QAS106 shared antigenic determinants with both the serovar 3 and 15 reference strains. Strain QAS106 was positive in the capsular serovar 12–specific polymerase chain reaction (PCR) assay, while the PCR toxin gene profiling and omlA PCR typing assay… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 21 publications
0
14
0
Order By: Relevance
“…A serovar 3 isolate recovered in Germany and Switzerland did not contain the apxIICA operon, only the apxIIICABD operon . A serovar 12 isolate from Japan had the toxin profile of serovar 3 with operons apxIICA and apxIIICABD , instead of being positive for apxIBD and apxIICA , which was the expected profile . It was hypothesised that the strain was originally a serovar 3 that had acquired the capsular polysaccharide biosynthesis genes specific for serovar 12 …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…A serovar 3 isolate recovered in Germany and Switzerland did not contain the apxIICA operon, only the apxIIICABD operon . A serovar 12 isolate from Japan had the toxin profile of serovar 3 with operons apxIICA and apxIIICABD , instead of being positive for apxIBD and apxIICA , which was the expected profile . It was hypothesised that the strain was originally a serovar 3 that had acquired the capsular polysaccharide biosynthesis genes specific for serovar 12 …”
mentioning
confidence: 99%
“…8 A serovar 12 isolate from Japan had the toxin profile of serovar 3 with operons apxIICA and apxIIICABD, instead of being positive for apxIBD and apxIICA, which was the expected profile. 9 It was hypothesised that the strain was originally a serovar 3 that had acquired the capsular polysaccharide biosynthesis genes specific for serovar 12. 9 In Australia, the most common serovars of A. pleuropneumoniae are 1, 5, 7 and 15.…”
mentioning
confidence: 99%
“…In order to elucidate the molecular basis of the serologic nontypeability of these 2 isolates, the gene clusters involved in the biosynthesis of CPS and O-PS were PCR-amplified from isolates IB19-1 and/or IB19-2. The primer pairs used for amplification of the cps 2 and o-ps 6,20 genes were designed from previously published sequences (Suppl. Table 1).…”
mentioning
confidence: 99%
“…In Japan, disease due to A. pleuropneumoniae serovar 15 has been found in Chiba, Ehime, Fukuoka, Hokkaido and Kagawa prefectures of Japan, and this serovar is the fourth most predominant serovar behind serovars 2, 1 and 5 [8, 14, 16, 23]. Recently, there have been several reports on field strains of A. pleuropneumoniae that do not possess the typical toxin profile associated with their serovar [1, 9, 13, 15, 26]. An earlier report [13] that used immunoblot analysis with monoclonal antibodies to detect toxin production reported that one field strain each of serovars 2 and 9 expressed ApxII only, while two field strains of serovar 7 expressed both ApxII and ApxIII.…”
mentioning
confidence: 99%
“…[15] reported that some field strains of serovar 3 isolated in Germany and Switzerland did not contain the apxIICA genes, and Ito et al . [9] found a Japanese strain of serovar 12 harboring apxIICA, apxIIICA and apxIIIBD genes, but not apxICA or apxIBD genes. A more recent study [26] that used the apx-based PCR methods to examine the Apx toxin profiles reported that some Australian field isolates of serovar 15 did not contain apxIICA genes.…”
mentioning
confidence: 99%